2021
DOI: 10.1093/jn/nxab248
|View full text |Cite
|
Sign up to set email alerts
|

Pecan-Enriched Diets Alter Cholesterol Profiles and Triglycerides in Adults at Risk for Cardiovascular Disease in a Randomized, Controlled Trial

Abstract: Background Research indicates that tree nuts are cardioprotective, but studies on pecans are limited. Objectives We examined the impact of daily pecan consumption on blood lipids and glycemia in adults at-risk for cardiovascular disease (CVD). Methods This was a randomized, controlled trial where 56 adults (BMI ≥28 kg/m2 or hypercholesterolemia) were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…However, not all nut studies have shown metabolic improvements because 2.5–6 months of daily almond consumption did not improve markers of energy metabolism 21,22 . Therefore, this preliminary research indicates that tree nuts and peanuts may increase RMR, DIT and fat oxidation, although more research is needed to confirm this notion, particularly in pecans where beneficial effects have been observed on blood lipid profiles but no metabolic research exists 23,24 …”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…However, not all nut studies have shown metabolic improvements because 2.5–6 months of daily almond consumption did not improve markers of energy metabolism 21,22 . Therefore, this preliminary research indicates that tree nuts and peanuts may increase RMR, DIT and fat oxidation, although more research is needed to confirm this notion, particularly in pecans where beneficial effects have been observed on blood lipid profiles but no metabolic research exists 23,24 …”
Section: Introductionmentioning
confidence: 83%
“…Following anthropometrics, participants then consumed a SFA‐rich, high‐fat breakfast shake within 10 min. This meal provided 17% of total daily energy needs and was made from an original milk chocolate ready‐to‐drink shake (Ensure; Abbott Nutrition) with added fat sources as previously described 24 . The nutrient breakdown of this test meal is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations